The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Section: 242 p. ; 23 cm
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences

Le harem et l'Occident - Mernissi, Fatima (Albin Michel, 2001)
"En Occident, le harem est représenté comme un lieu de plaisir où s'ébattent des femmes nues et lascives, odalisques d'Ingres et de Matisse, Schéhérazade en version hollywoodienne. En Orient, le harem est au contraire le lieu de la réclusion des femmes qui ne rêvent que de s'en émanciper, en jouant de leur talent et de leur intelligence, qu'elles aient vécu au temps du khalife Haroun Al-Rachid ou dans le harem domestique des années 50 à Fès. Ces deux représentations du harem - l'une fantasmée, l'autre historique - dessinent une vision différente, troublante et inattendue, non seulement de "la femme idéale" mais aussi de la séduction, de l'érotisme et des rapports entre les sexes. "Décris-moi ton harem, je te dirai qui tu es", semble nous suggérer avec humour Fatema Mernissi, bien connue du public pour sa vision aussi pertinente qu'impertinente d'un monde arabe en pleine mutation. Le Harem et l'Occident : un fascinant voyage au coeur des harems, un face à face revigorant entre les cultures autant qu'une méditation sur le pouvoir de l'image et la perception de soi."–Quatrième de couverture.
Section: 230 pages ; 23 cm
Keywords: 1800-1899; 1900-1999; afrique; approches et analyses; cours; discipline; fantasme; féminisme arabe; féminisme islamique; histoire et politique; maghreb; maroc; premier cycle; périodes historiques; representation; régions géographiques; sciences humaines; sex2283; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; violences